The departure of the hero in a ship: The intertextuality of Beowulf, Cynewulf and Andreas - Leneghan, F (Oviedo University Press, 2019)
This article identifies a new Old English poetic motif, ‘The Departure of the Hero in a Ship’, and discusses the implications of its presence in Beowulf, the signed poems of Cynewulf and Andreas, a group of texts already linked by shared lexis, imagery and themes. It argues that the Beowulf-poet used this motif to frame his work, foregrounding the question of royal succession. Cynewulf and the Andreas-poet then adapted this Beowulfian motif in a knowing and allusive manner for a new purpose: to glorify the church and to condemn its enemies. Investigation of this motif provides further evidence for the intertextuality of these works.